2002
DOI: 10.1002/ana.10096
|View full text |Cite
|
Sign up to set email alerts
|

Familial cardioneuromyopathy with hyaline masses and nemaline rods: A novel phenotype

Abstract: Two siblings (patients 1 and 2) had adult-onset muscle weakness that was greater distally than proximally, as well as respiratory insufficiency, cardiomyopathy, and cervical spine anomalies. Electromyography studies indicated myopathy and findings consistent with neuropathy in both. In the deltoid muscle of patient 1 and the anterior tibial muscle of patient 2, myriad type 1 fibers harbored large, irregularly polygonal, and mostly central hyaline masses, small vacuoles, and nemaline rods flanking the hyaline m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Autoantibody testing has not been previously reported in this disease, but a case in which ANA positivity along with a muscle biopsy showing inflammation led to a mistaken diagnosis of PM has been described [8]. The myopathy in Patient 2 is less well-defined pathologically but resembles the syndrome of hyaline masses and nemaline rods recently described in familial cardioneuromyopathy [4]. Autoantibody studies have not been reported in this syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoantibody testing has not been previously reported in this disease, but a case in which ANA positivity along with a muscle biopsy showing inflammation led to a mistaken diagnosis of PM has been described [8]. The myopathy in Patient 2 is less well-defined pathologically but resembles the syndrome of hyaline masses and nemaline rods recently described in familial cardioneuromyopathy [4]. Autoantibody studies have not been reported in this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The sedimentation rate and CK were within normal ranges. A quadriceps muscle biopsy showed desmin-reactive hyaline bodies in the sarcoplasm of multiple myofibers, compatible with myofibrillar myopathy [4] (Figure 2). Intermittent prednisone treatment resulted in slight improvement, but she remained very weak.…”
Section: Case Reportmentioning
confidence: 99%
“…It inhibits apoptosis by preventing the activation of procaspase 3, in which process phosphorylation of Ser59 is essential [19–21]. Ample evidence indicates the involvement of αB‐crystallin in the ubiquitin proteasome system [17,22–25], and in the aggresomal response to misfolded proteins in degenerative neuro‐ and myopathies [26–33].…”
mentioning
confidence: 99%
“…Other gene defects implicated in nemaline myopathy comprise the slow α‐tropomyosin 3 gene at 1q22‐23, 199,200 the β‐tropomyosin 2 gene, 201 the troponin T1 gene, 202 and the sarcomeric actin gene at 1q42 187,203 , 204 . There has been also an association between nemaline rods and hyaline masses reported in a familial cardioneuromyopathy with adult onset 205 …”
Section: Nemaline Myopathymentioning
confidence: 99%